The theoretical and methodological problems of PR (Herald of Journalism, 2020)
Based on the works of American, Turkish, Russian, local and Western researchers in this article reveals the theoretical and methodological issues of PR. Using specific examples, compare the similarities and differences in public relations and advertising, between public relations and propaganda. The author makes it clear how public relations are directly related to soci- ology, economics, law, cultural studies, management, politics, journalism, sociology.
Keywords: PR, marketing, advertising, propaganda.